The concept of Botho and HIV & AIDS in Botswana - Gaie, Joseph B. R.; Mmolai, Sana (Zapf Chancery, 2007)
Ever since the publication of Placide Tempel's epoch-making work Bantu Philosophy, African philosophers have worked to dispel the myth that there is no metaphysics in Africa. In the East African context we remember the names of Joseph Nyasmi and Odera Oruka, and in the West African context, Pauline Hotoundji and Kwesi Wiredu have made monumental contributions to elucidate African metaphysics. This compendium, presented by a group of scholars from the University of Botswana, seeks to build bridges between the seemingly estranged disciplines of African metaphysics, existential philosophy, and ec
Keywords: AIDS; AIDS & HIV; AIDS (Disease); Bioethics; Botswana; Diseases AIDS & HIV; HEALTH & FITNESS; HIV infections; MEDICAL; Manners and customs; Medical ethics; PHILOSOPHY / Metaphysics; Philosophical anthropology; Religion; Religious aspects; Social life and customs